Bank Sampah: Sumber Pendapatan Sekunder Ibu Rumah Tangga Warga RW 20 Kelurahan Jember Kidul - Regina Niken Wilantari; Sebastiana Viphindrartin; Okyviandi Putra Erlangga; Rafael Purtomo Somaji; Nanik Istiyani (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Household waste is an environmental problem for the community, especially urban areas, which until now has no solution. The limited number of landfills in Jember Regency makes this waste problem even more complex. Waste Bank seems to be a promising alternative to waste management strategy. Community service activities by establishing a waste bank as the main program in partnership with Housewives of RW 20 Kelurahan Jember Kidul where there are around 58 households. Several problems are faced by partners, such as a lack of knowledge regarding the negative impacts of waste and not knowing anything about waste banks, how they work, and generating income just by sorting and depositing them in the waste bank. The method used in community service is Community Based Participatory Research (CBPR) by guiding the housewives of the RW 20 Kelurahan Jember Kidul to be actively involved in waste management training. The target to be achieved from this activity is that the people of RW 20 Kelurahan Jember Kidul are educated to sort waste and deposit waste into the Waste Bank to create a clean and healthy environment and increase the income of households. The district government is expected to be actively involved so that the program can run sustainably